2018
DOI: 10.1038/s41419-018-1207-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen affects the negative feedback loop of PTENP1-miR200c to inhibit PTEN expression in the development of endometrioid endometrial carcinoma

Abstract: Endometrial carcinoma is one of the most common malignancies in the female reproductive system. It is well-known that estrogen plays an important role in the pathogenesis of endometrioid endometrial carcinoma (EEC), and induces the cancer suppressor gene PTEN deletion. However, how estrogen affects PTEN expression remains unknown. In the present study, we found in 40 EEC specimens, miR-200c level was higher in most cancer areas than that in the adjacent normal endometrium, while PTEN and PTENP1 were lower. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…The miR-200 family is implicated in the PI3K/AKT/mTOR signaling pathway, at least in part through downregulation of the PTEN tumor suppressor [ 141 , 142 , 143 ]. This was recently confirmed by Chen et al who reported that miR-200c binds directly to PTEN and PTENP1 in endometrioid EC [ 102 ]. In agreement, a different study reported that estrogen stimulation increases the expression of miR-200c which is accompanied by decreased PTEN expression and activation of the PI3K-AKT pathway thereby promoting increased cellular survival [ 67 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The miR-200 family is implicated in the PI3K/AKT/mTOR signaling pathway, at least in part through downregulation of the PTEN tumor suppressor [ 141 , 142 , 143 ]. This was recently confirmed by Chen et al who reported that miR-200c binds directly to PTEN and PTENP1 in endometrioid EC [ 102 ]. In agreement, a different study reported that estrogen stimulation increases the expression of miR-200c which is accompanied by decreased PTEN expression and activation of the PI3K-AKT pathway thereby promoting increased cellular survival [ 67 ].…”
Section: Discussionsupporting
confidence: 59%
“…They are frequently detected in patients with aberrant methylation of the MLH1 promoter regions that cause inactivation of the mismatch repair (MMR) gene [ 164 , 165 ]. The miR-200 family, miR-183 and miR-21 have been shown to target the PTEN gene, and their expression levels in endometrial tissue can be used to predict the risk of tumor progression from endometrial hyperplasia to invasive EC [ 102 , 122 ]. TP53 mutations, corresponding to the “Copy Number High” subgroups, are more common in grade 3 tumors, which are associated with poorer survival than other tumor groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudogenes most likely impact their parental gene expression via ceRNA network in which pseudogene RNAs interact with their counterparts through competitively binding to common miRNAs and attenuate repression on the parental genes [25]. In this context, pseudogene PTENP1 up-regulated its parental gene PTEN expression by sponging miR-19b, miR-21, miR-193-3p and miR-200c [2629]. In this study, we observed that RP11-424C20.2 expression was strongly correlated with its parental gene UHRF1 expression in 8 types of human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 In endometrial carcinoma, estrogen contributes to carcinogenesis by activating ERα, which subsequently activates the downstream signaling pathways of phosphatidylinositol 3-kinase (PI3K)/ AKT and mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) (Figure 3). 69,71 In ER+ breast cancer, estrogen activates the PI3K/AKT/mTOR signaling pathway by associating with extra-nuclear ERα, which results in drug resistance and epithelial-to-mesenchymal transition (EMT) (Figure 3). 70,72 Targeting ERα reportedly causes changes in the expression of components of the PI3K/AKTprotein kinase Cα signaling pathway, resulting in cell apoptosis.…”
Section: Erα and Signaling Pathwaysmentioning
confidence: 99%